Genetic Variation in Mhc Class II B in Atlantic Salmon: Evolutionary and Ecological Perspectives - Langefors, Åsa (Department of Animal Ecology, Lund University, 1999)
The Major Histocompatibility Complex (Mhc) genes are crucial for the recognition of self and non-self peptides by the immune defence system. They are extremely variable in most studied vertebrate species. I have studied the extent and the importance of Mhc variation in Atlantic salmon (Salmo salar), mainly from the Baltic Sea. Levels of Mhc heterozygosity in hatchery populations of salmon were between 0.5 and 0.8, the lowest values in a hatchery where a lower annual number of breeders were used. In a wild, naturally spawning population, heterozygosity was 0.7, which is in between the levels observed in the hatcheries. The origin and maintenance of the high level of Mhc variation is a contentious issue. My results show that there is only one single Mhc class II B gene in Atlantic salmon, and indicate that point mutations are not the sole origin of variation in this single gene. New alleles appear to result from recombination. Mhc variation is assumed to be maintained by some kind of balancing selection, which is supported by my results. Balancing selection may be in terms of over-dominance selection (heterozygote advantage) or frequency dependent selection. I have not found any support for over-dominance selection. I found that certain Mhc alleles were associated with furunculosis, a bacterial infection as well as the syndrome M74, which has caused high mortality in Baltic Sea salmon. There was however, no association between heterozygosity and either furunculosis or M74. These results, together with the lack of an excess of heterozygous individuals in the natural population, support that frequency dependent selection rather than over-dominant selection, is the main mechanism for maintaining Mhc variation.